Pengaruh Komitmen Organisasi, Beban Kerja Dan Komunikasi Terhadap Kinerja Karyawan Pada Cv. Yamaha Waja Motor Cabang Hayam Wuruk Denpasar - Tiksnayana Vipraprastha; Bagus Nyoman Kusuma Putra (Universitas Triatma Mulya, 2025)
The purpose of this study was to determine whether organizational commitment, workload and communication affect employee performance at CV.Waja Motor Cabang Hayam Wuruk Denpasar. Samples were collected using saturated sampling techniques totaling 36 respondents. The data analysis technique used in this study was multiple regression analysis. The results of the study indicate that: (a) there is a significant and positive influence between organizational commitment and employee performance with a coefficient value of 0.530 and a significance value of 0.034, (b) there is a significant and positive influence between workload and employee performance with a coefficient value of 0.872 and a significance value of 0.010, and (c) there is a significant and positive influence between communication and employee performance with a coefficient value of 0.505 and a significance value of 0.009.